Cold Tom : a novel - Prue, Sally (New York : Scholastic Press, 2003)
Struggling to find a place for himself, Tom flees the elven parents who hunt to kill him and becomes involved with human "demons" in the nearby city.
Originally published: Oxford, England : Oxford University Press, 2001.
Keywords: Elves -- Juvenile fiction; Identity -- Juvenile fiction; Fantasy fiction